(untitled) (ACME, 2024)
The research conducted among the private papers of the Piedmontese lexicographer Giacinto Carena, preserved at the Academy of Sciences of Turin, made it possible to trace a vast quantity of unpublished materials of historical-linguistic interest. In addition to the correspondence (with around 200 correspondents, including Manzoni, who sent him the well-known letter Sulla lingua italiana, Cherubini, Cantù, Gherardini), the travel diaries are preserved, which show the evolution of his interests in scientific nomenclature , and the preparatory notes for the Prontuario di vocaboli that Carena published in 1846 and 1853 and which was followed by a third posthumous part in 1860. The essay intends to give an account of the material present in the Carena collection, trying to capture the different phases of his lexicological and onomasiological study in the diaries and private writings; how his idea of composing a vocabulary based on the Tuscan language was formed; with what methods he collected the information from the voice of his interlocutors; how he arranged the material collected during numerous field explorations.